REQUIEM FOR THE PROTESTANT CENTRAL BOARD OF EXAMINERS - Jefferis, J.D. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1971)
It was in November 1886 that the Protestant Committee of the Council of Public Instruction for Quebec recommended the appointment of a Central Board of Examiners, "composed of men of the requisite knowledge and skill for conducting the examinations," to replace the local Boards which, at that time, were charged with the certification to teachers.